Effect of triftazin (trifluoperazine) on the symptoms of autism spectrum disorders in rats with fetal valproatate syndrome - I. G. Kapitsa; E. A. Ivanova; T. A. Voronina; G. V. Protsun (LLC "Publisher OKI", 2017)
The effect of triftazin (trifluoperazine) on social interaction abnormalities as a main feature of autism spectrum disorders, exploratory behavior and learning capacity was studied in rats with fetal valproatate syndrome. It was shown that triftazin at a dose of 0,35 mg/kg does not affect the deficit of social interaction, spatial learning or memory but improves exploratory activity by decreasing anxiety in rats with fetal valproate syndrome.